2013
DOI: 10.1016/j.bandc.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional hemispheric asymmetries of global/local processing mirrored by the steady-state visual evoked potential

Abstract: While hemispheric differences in global/local processing have been reported by various studies, it is still under dispute at which processing stage they occur. Primarily, it was assumed that these asymmetries originate from an early perceptual stage. Instead, the content-level binding theory (Hübner & Volberg, 2005) suggests that the hemispheres differ at a later stage at which the stimulus information is bound to its respective level. The present study tested this assumption by means of steady-state evoked po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Neuroimaging studies have demonstrated that the posterior parietal cortex area contributes as a key locus of storage of representation of visual information and is associated with feature identification in spatial stimuli processing [60,62,74-76]. Furthermore, many previous studies had indicated that the left temporo-parietal regions attend to local aspect of an object’s shape [12,13,15,77-79]. Regarding human visual system, objects within the visual scene are inclined to be identified and perceived as a whole [10,80], and this global perception tendency would dominate during EFT.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies have demonstrated that the posterior parietal cortex area contributes as a key locus of storage of representation of visual information and is associated with feature identification in spatial stimuli processing [60,62,74-76]. Furthermore, many previous studies had indicated that the left temporo-parietal regions attend to local aspect of an object’s shape [12,13,15,77-79]. Regarding human visual system, objects within the visual scene are inclined to be identified and perceived as a whole [10,80], and this global perception tendency would dominate during EFT.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at a forest, one can view it holistically in its global meaning (a forest), or focus on specific trees and attend to their local features. Many studies with healthy and brain-damaged patients have demonstrated that these two complementing modes of perception are lateralized in the brain; the RH mediates the grasp of the overall picture, while the LH is associated with attention to the details [275, 276, 277, 278, 279, 280, 281, 282, 283, 284, 285]. For instance, patients with a unilateral brain damage were shown a series of stimuli (letters or geometrical shapes) consisting of elements which had different meanings than the global feature (see example in Fig.…”
Section: Abnormal Social Behaviorsmentioning
confidence: 99%
“…One obvious explanation may be that the VF effects captured with Navon's paradigm are small, and that failures to find them could reflect low statistical power (Lamb & Yund, 1996;Martens & Hübner, 2013).…”
Section: Introductionmentioning
confidence: 99%